Choline and nicotine increase glioblastoma cell proliferation by binding and activating α7- and α9- containing nicotinic receptors. (January 2021) - Pucci, Susanna; Fasoli, Francesca; Moretti, Milena; Benfante, Roberta; Di Lascio, Simona; Viani, Paola; Daga, Antonio; Gordon, Thomas J.; McIntosh, Michael; Zoli, Michele; Clementi, Francesco; Gotti, Cecilia
Graphical abstract: Highlights: Choline compounds are highly increased in glioblastoma cells. Choline is also an agonist of α7- and α9-containing nicotinic receptors. Both choline and nicotine promote glioblastoma cell proliferation and survival. These effects are blocked by specific nicotinic antagonists or α7- and/or α9 siRNAs. Nicotinic antagonists also decrease basal glioblastoma cell proliferation. Abstract: Glioblastomas (GBMs), the most frequent and aggressive human primary brain tumours, have altered cell metabolism, and one of the strongest indicators of malignancy is an increase in choline compounds. Choline is also a selective agonist of some neuronal nicotinic acetylcholine receptor (nAChR) subtypes. As little is known concerning the expression of nAChR in glioblastoma cells, we analysed in U87MG human grade-IV astrocytoma cell line and GBM5 temozolomide-resistant glioblastoma cells selected from a cancer stem cell-enriched culture, molecularly, pharmacologically and functionally which nAChR subtypes are expressed and, whether choline and nicotine can affect GBM cell proliferation. We found that U87MG and GBM5 cells express similar nAChR subtypes, and choline and nicotine increase their proliferation rate and activate the anti-apoptotic AKT and pro-proliferative ERK pathways. These effects are blocked by the presence of non-cell-permeable peptide antagonists selective for α7- and α9-containing nicotinic receptors. siRNA-mediated silencing of α7 or α9 subunit expression also selectively prevents the effects of nicotine and choline on GBM cell proliferation. Our findings indicate that nicotine and choline activate the signalling pathways involved in the proliferation of GBM cells, and that these effects are mediated by α7 and α9-containing nAChRs. This suggests that these nicotinic receptors may contribute to the aggressive behaviour of this tumor and may indicate new therapeutic strategies against high-grade human brain tumours.